Analisis Pengaruh Laba Akuntansi, Arus Kas Operasi, Arus Kas Pendanaan, Debt to Equity Ratio, Current Ratio dan Risiko Saham Terhadap Return Saham - Sulaiman Sulaiman; Iman S. Suriawinata (Jurnal Ekonomi, 2020)
The purpose of this study was to determine and examine the effect of Accounting Profit, Operating Cash Flow, Funding Cash Flow, Debt to Equity Ratio, Current Ratio, and Stock Risk on Stock Returns in Companies Listed in LQ45 on the IDX for the 2014-2017 period. The population in this study were 45 companies listed in the LQ45 index as of February 2019, while the sample in this study was 18 companies determined by the purposive sampling technique. Data analysis using eviews 8.0. The results showed that accounting profit had a positive effect on stock returns. Operating cash flow has a positive effect on stock returns. Funding cash flow has no positive effect on stock returns. Debt to equity ratio has no negative effect on stock returns. Current Ratio has a positive effect on stock returns, and stock risk has a positive effect on stock returns of companies listed in LQ45 on the IDX for the 2014-2017 period.